2012
DOI: 10.3109/00365521.2012.737360
|View full text |Cite
|
Sign up to set email alerts
|

Propofol combined with traditional sedative agents versus propofol- alone sedation for gastrointestinal endoscopy: a meta-analysis

Abstract: PTSA sedation during gastrointestinal endoscopy could significantly reduce the total dose of propofol, but without benefits of lower risk of cardiopulmonary complications compared with propofol-alone sedation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 25 publications
1
23
0
1
Order By: Relevance
“…Cardiopulmonary adverse events, such as hypoxia, hypotension, arrhythmia, and apnea, are concerns regarding propofol sedation in cirrhotic patients because propofol exhibits greater suppressive cardiopulmonary effects than midazolam does. A previous meta-analysis compared using propofol combined with other sedative agents to sedate patients undergoing GIE with sedation using propofol alone, and determined that administering a higher dose of propofol did not increase the risk of cardiopulmonary adverse events [ 33 ]; this observation is consistent with our findings that propofol sedation does not increase the risk of bradycardia, hypotension, or hypoxemia compared with midazolam sedation. Sedatives used for UGIE can be administered by anesthesiologists, gastroenterologists, and trained registered nurses.…”
Section: Discussionsupporting
confidence: 90%
“…Cardiopulmonary adverse events, such as hypoxia, hypotension, arrhythmia, and apnea, are concerns regarding propofol sedation in cirrhotic patients because propofol exhibits greater suppressive cardiopulmonary effects than midazolam does. A previous meta-analysis compared using propofol combined with other sedative agents to sedate patients undergoing GIE with sedation using propofol alone, and determined that administering a higher dose of propofol did not increase the risk of cardiopulmonary adverse events [ 33 ]; this observation is consistent with our findings that propofol sedation does not increase the risk of bradycardia, hypotension, or hypoxemia compared with midazolam sedation. Sedatives used for UGIE can be administered by anesthesiologists, gastroenterologists, and trained registered nurses.…”
Section: Discussionsupporting
confidence: 90%
“…This study revealed that propofol TCI combined with midazolam/fentanyl versus propofol TCI alone reduced propofol dosage, produced less hypotension and shortened recovery time and discharge time. When propofol was administrated with intermittent bolus method, many reports showed that propofol combined with traditional sedation agents during GI endoscopy could significantly reduce the total dose of propofol compared with propofol‐alone sedation [17,21–23]. Hsieh et al [23] compared intermittent bolus propofol alone and propofol in combination with meperidine and found that the combination regimen is better in improving tolerance and recovery for sedated colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, TCI provides a more precise control of propofol concentration than the intermittent bolus methods, which result in many peaks and troughs of propofol level. Only limited reports have investigated propofol TCI in sedated GI endoscopy [13–15]; instead, propofol was administrated by intermittent bolus methods in most nonanesthesiologist practices [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Although a smaller proportion of patients in the study by Leslie et al received propofol in combination with opioids (fentanyl or alfentanyl), the weight-adjusted doses were similar in both studies (0.78 vs. 0.77 mcg.kg -). In addition, 37% of patients in the aforementioned study also received 2 mg of midazolam during anaesthesia induction, which has been proven to reduce propofol consumption [15,16]. Therefore, the lower administered doses of propofol in the study by Leslie et al could probably be attributed to the addition midazolam and not opioids to the anaesthetic regimen.…”
Section: Discussionmentioning
confidence: 93%